HUBUNGAN ANTARA KONSEP DIRI DAN PERILAKU KONSUMTIF PADA MAHASISWA UNIVERSITAS KRISTEN SATYA WACANA SALATIGA - Arik Dyah Ayu Lestari,; Emmanuel Satyo Yuwono, (Juremi: Jurnal Riset Ekonomi, 2024)
This research aims to investigate the relationship between self-concept and consumptive behavior among active students at UKSW Salatiga. This study employs a non-probability sampling technique known as quota sampling. The subjects involved in this research consist of 115 active students at UKSW Salatiga. Data collection methods utilize the Self-Concept Scale and Consumptive Behavior Scale. The data analysis method utilized is the Pearson product-moment correlation. From the analysis results, a correlation coefficient of -0.209 was obtained with a p-value of 0.025 (p<0.05). From these results, it can be concluded that there is a significant negative relationship between self-concept and consumptive behavior among active students at UKSW Salatiga. Thus, it is evident that the higher the level of self-concept among students, the lower their level of consumptive behavior. Conversely, the lower the self-concept among students, the higher their consumptive behavior tends to be